High‐Performance Transition Metal Dichalcogenide Photodetectors Enhanced by Self‐Assembled Monolayer Doping. (26th May 2015) - Kang, Dong‐Ho; Kim, Myung‐Soo; Shim, Jaewoo; Jeon, Jeaho; Park, Hyung‐Youl; Jung, Woo‐Shik; Yu, Hyun‐Yong; Pang, Chang‐Hyun; Lee, Sungjoo; Park, Jin‐Hong
Abstract : Most doping research into transition metal dichalcogenides (TMDs) has been mainly focused on the improvement of electronic device performance. Here, the effect of self‐assembled monolayer (SAM)‐based doping on the performance of WSe2 ‐ and MoS2 ‐based transistors and photodetectors is investigated. The achieved doping concentrations are ≈1.4 × 10 11 for octadecyltrichlorosilane (OTS) p‐doping and ≈10 11 for aminopropyltriethoxysilane (APTES) n‐doping (nondegenerate). Using this SAM doping technique, the field‐effect mobility is increased from 32.58 to 168.9 cm 2 V −1 s in OTS/WSe2 transistors and from 28.75 to 142.2 cm 2 V −1 s in APTES/MoS2 transistors. For the photodetectors, the responsivity is improved by a factor of ≈28.2 (from 517.2 to 1.45 × 10 4 A W −1 ) in the OTS/WSe2 devices and by a factor of ≈26.4 (from 219 to 5.75 × 10 3 A W −1 ) in the APTES/MoS2 devices. The enhanced photoresponsivity values are much higher than that of the previously reported TMD photodetectors. The detectivity enhancement is ≈26.6‐fold in the OTS/WSe2 devices and ≈24.5‐fold in the APTES/MoS2 devices and is caused by the increased photocurrent and maintained dark current after doping. The optoelectronic performance is also investigated with different optical powers and the air‐exposure times. This doping study performed on TMD devices will play a significant role for optimizing the performance of future TMD‐based electronic/optoelectronic applications. Abstract : High‐performance transition metal dichalcogenides (TMD) photodetectors are enhanced by self‐assembled monolayer (SAM) doping. The photoresponsivity of WSe2 and MoS2 photodetectors is improved by a factor of ≈28.2 (with OTS p‐doping) and ≈26.4 (with APTES n‐doping), respectively. These improvements are attributed to the enhancement of TMD optical properties by SAM doping and this is also investigated in detail through photoluminescence analysis.